Development of a Critical Nitrogen Dilution Curve of Double Cropping Rice in South China - He, Zhiyuan; Qiu, Xiaolei; Ata-Ul-Karim, Syed Tahir; Li, Yanda; Liu, Xiaojun; Cao, Qiang; Zhu, Yan; Cao, Weixing; Tang, Liang (Frontiers in Plant Science, 2017)
The concept of critical nitrogen (Nc) concentration can be implemented to diagnose in-season plant nitrogen (N) status for optimizing N fertilizer management. The Nc dilution curves have been established for rice (Oryza sativa L.) grown in different climatic regions, yet no attempt has been made to develop the Nc dilution curve for double cropping rice regions. This study was undertaken to develop the Nc dilution curves for double cropping rice in south China for assessment of in-season N status and to establish the relationships N nutrition index (NNI) and relative yield (RY) for in-season prediction of rice grain yield. Three different N application rate field experiments using six Indica rice varieties, including two early rice hybrids and four late rice hybrids were carried out in east China. The Nc dilution curves based on whole plant N concentration were determined and described as, Nc=3.37W-0.44 for early rice and Nc=3.69W-0.34 for late rice. The constant N concentration at early growth stage was 3.31 and 3.15% DM for early and late rice, respectively. Late rice showed a higher capacity of N accumulation and a lower rate of N decline per unit shoot biomass as compared to early rice. The curves for present study were different from the existing reference curves for Indica and Japonica rice grown in different rice growing regions. Integrated N nutrition index (NNIint) based on Nc was used to estimate RY at different growth periods using linear regression functions. The results showed that the critical curves and relationship between NNIint and RY could be used as a reliable indicator of N status diagnosis, grain yield prediction as well as to provide technical support in N management for double cropping rice in south China.